A new hypogean species of the genus Domene Fauvel, 1873 from Turkey (Coleoptera: Staphylinidae: Paederinae). Issue 1 (2nd January 2019) - Anlaş, Sinan
Abstract : Domene bordonii sp. n. is described and illustrated from Geyik Mountains, Konya province, central southern Anatolia. This new hypogean species was collected with a subterranean pitfall trap in the mesovoid shallow substratum. http://www.zoobank.org/urn:lsid:zoobank.org:pub:72D06EC5-885F-4BCC-8066-A16B28016697